Strategi Pemasaran Agribisnis Ikan Nila Dalam Di Kecamatan Babirik Kabupaten Hulu Sungai Utara - Rum Van Royensyah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2013)
This study aims to analyze the strategy of developing tilapia agribusiness in Babirik District, North Hulu Sungai Regency. Sampling was done by multi stage sampling and the selection of sub-district locations was carried out by purposive sampling method, namely the sub-districts which most cultivated tilapia in karamba, namely Babirik District. Fish farmers as samples were selected by stratified proportional random sampling, as many as 8 people (30% of 27 UPP group members), and 57 people (30% of 191 were not UPP group members). The number of samples is 65 people. Collector samples (collectors) were selected by snow ball sampling, which was 20 people (30% of 65 collectors). The sample of retailers was chosen by accidental sampling in the fish market in North Hulu Sungai Regency, as many as 5 people. The selection of Fisheries UPP internal factor samples was 8 people (30% of 27 people), and the sample selection of non Fisheries UPP internal factors was 20 people (30% of 191 people), while 2 external factors were selected from the relevant institutions. The results of the internal factor evaluation matrix are 3,163, while the results of the external factor evaluation matrix are 2,538. The results of the internal external matrix are in cell IV, namely in the growth and building position, and the indigo agribusiness strategy in karamba in Babirik District is a market development and production strategy.